2022
DOI: 10.1097/scs.0000000000008626
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Removal of a Nasopharyngeal Foreign Body Stuck Within the Sphenoid Bone Using the Endonasal Transseptal Approach

Abstract: : Nasopharyngeal foreign bodies (FBs), which are generally caused by a strong, external force, are seldomly encountered. Removing these FBs is challenging for otorhinolaryngological surgeons because of the vital structures surrounding the nasopharynx, such as the skull base, cranial nerves, and internal carotid artery. Here, the authors report the case of a 69-year-old man referred to our hospital after accidentally cutting his face while using a grinder. Grinder fragments were deeply embedded in the face, thu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Consequently, the presence of a guide appeared to have a minimal impact on the successful outcomes. Furthermore, there have been reports on the combined use of navigation systems and endoscopy 8 . Given the deep-seated nature of the foreign bodies in our patient relative to the incision site, it is plausible to anticipate favorable outcomes with an endoscope.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Consequently, the presence of a guide appeared to have a minimal impact on the successful outcomes. Furthermore, there have been reports on the combined use of navigation systems and endoscopy 8 . Given the deep-seated nature of the foreign bodies in our patient relative to the incision site, it is plausible to anticipate favorable outcomes with an endoscope.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, there have been reports on the combined use of navigation systems and endoscopy. 8 Given the deep-seated nature of the foreign bodies in our patient relative to the incision site, it is plausible to anticipate favorable outcomes with an endoscope. However, a previous study demonstrated the utilization of separate incisions for navigation and endoscopy, thereby raising cosmetic concerns regarding the additional incisions.…”
Section: Discussionmentioning
confidence: 99%
“…Key Words: Dental implant, overdenture, segmental mandibulectomy, xeroderma pigmentosum X eroderma pigmentosum (XP) is a rare hereditary disease, an autosomal recessive disorder with extreme sensitivity to sunlight resulting in changes in the skin and a significantly elevated incidence of skin cancers. 1 In Brazil, it is estimated that the existence of ~200 patients, which would represent 1 case per million inhabitants. 2 Patients with XP have greater than 10,000-fold risk over their lives of developing skin cancer compared with the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Penetrations of the zygoma through the nasal cavity by wooden foreign bodies are extremely rare and have not been reported yet. Generally, computed tomography (CT) is the most important radiologic modality to evaluate foreign bodies 1. In the case of wooden foreign bodies, different from any metal components, they are characterized as hypodense signals resembling air bubbles.…”
mentioning
confidence: 99%
See 1 more Smart Citation